Toward Collaborative Evidence Based Information Practices: Organisation and Leadership Essentials - Mirijamdotter, Anita (Evidence Based Library and Information Practice, 2010)
This commentary is based on my key note for the EBLIP conference held in 2009 in Stockholm, Sweden. The title was: Bridging the gap between users and systems – the potential contribution of Social Informatics to Evidence Based Library and Information Practice. In the following commentary, I focus on the application of social informatics principles to develop a collaborative evidence based approach grounded in shared workplace leadership. My remarks highlight some main contributions from the field of library and information science and social informatics and conclude with implications for practice, including further research.